Development and validation of a novel sodium-overload related genes signature for prognostic prediction in breast cancer: integrating bioinformatics and experimental approaches - Feng, Qizhen; Yang, Wenlin; Su, Guohao; Wu, Fei; Xing, Chungen (Frontiers in Immunology, 2025)
IntroductionNecrosis induced by sodium overload has recently been identified as a novel form of regulated cell death. However, the specific genes associated with sodium overload in breast cancer (BC) remain uncharacterized.MethodsWe identified 753 differentially expressed sodium-overload-related genes (DESORGs) in BC. We performed pathway enrichment analyses, then used univariate Cox regression to select 67 prognostic DESORGs. To build prognostic models, we tested 101 combinations of ten machine learning algorithms. SHAP analysis was used to determine feature importance. Mendelian randomization (MR) was applied to assess causal effects. Experimental validation (in vitro) included overexpression and knockdown studies. GSEA/GSVA and molecular docking were conducted to explore downstream pathways and potential drug candidates.ResultsThe ridge regression model showed optimal prognostic power. IFNG was identified as the key feature. The computed risk score was an independent prognostic factor, outperforming traditional clinical variables (AUC = 0.845), and a nomogram built with it yielded good calibration (C-index = 0.815). MR suggested a protective causal effect of NR1H3 in BC, and patients with high NR1H3 expression had significantly better overall survival (p = 0.02). In vitro, NR1H3 overexpression suppressed proliferation, colony formation, migration, and invasion, whereas its knockdown had opposite effects. GSEA and GSVA showed that high NR1H3 expression is enriched in immune activation–related pathways. Molecular docking identified Cephaeline and Emetine as potential drugs that upregulate NR1H3 expression.ConclusionsThese findings highlight NR1H3 as a novel DESORG and a promising therapeutic target in breast cancer.